Applying Indigenous Research Methods: Storying with Peoples and Communities, 1st edition - Sweeney, Windchief (Routledge, 2020)
Applying Indigenous Research Methods focuseson the question of "How" Indigenous Research Methodologies (IRMs)can be used and taught across Indigenous studies and education.